Critical Christianity : translation and denominational conflict in Papua New Guinea - Handman, Courtney, 1975- (Anthropology of Christianity, 2015)
In Critical Christianity, Courtney Handman analyzes the complex and conflicting forms of sociality that Guhu-Samane Christians of rural Papua New Guinea privilege and celebrate as ""the body of Christ."" Within Guhu-Samane churches, processes of denominational schism-long relegated to the secular study of politics or identity-are moments of critique through which Christians constitute themselves and their social worlds. Far from being a practice of individualism, Protestantism offers local people ways to make social groups sacred units of critique. Bible translation, produced by members of the